Supply chain network design with coordinated inventory control. (January 2021) - Darmawan, Agus; Wong, Hartanto; Thorstenson, Anders
Highlights: It is important to consider inventory deployment in supply chain network design. Coordinated inventory control in network design generates cost savings. The heuristic developed helps facilitate the implementation of an integrated approach. Abstract: In this paper, we present models and solution methods for supply chain network design that not only integrate the location-transportation and inventory problems, but also consider the implementation of coordinated inventory control in the network. We compare two different strategies differentiated by whether or not coordinated inventory control is implemented. Due to the complexity of the optimization problems, we develop heuristic methods to solve the problems generated by the two strategies. The numerical results show the benefits of considering coordinated inventory control by reducing the inventory as well as the total costs in the supply chain network. The structure of the network can also be affected by the coordinated inventory control. The effects are most pronounced when the inventory holding cost rate is high.